Coherent Transition Radiation from Wire Metamaterials; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Naumenko G. A. Gennadiy Andreevich; Bleko V. V. Vitold Vladislavovich; Soboleva V. V. Veronika Vyacheslavovna; Shumeyko A. O. (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen